Treatment of AUD (Alcohol Use Disorder): the role of psychosocial approaches considering neuroplasticity and trauma aspects - Ina Maria Hinnenthal; Christian Chiamulera; Fabio Lugoboni; Roger Schmidt; Elisa Sgualdini; Mauro Cibin (Nutrimentum et Curae)
AUD can be treated in different settings, such as self-help groups, public health care ambulatories for addiction and therapeutic communities. Alcohol addiction must be considered a dysfunctional answer to an underlying emotional dysfunction or disorder. Psychosocial approaches must be personalized considering the diagnosis, psychosocial factors, level of resilience, neuroplastic aspects and trauma/negative life events in biography. Clinical aspects are enlightened, as well as the historical background of psychosocial approaches in Italy.